Improvement of a Method of the Pulse Windings Control of Aviation Direct Current Collector Generators - A. A. Sheinikov; Yu. V. Suchodolov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The analysis of direct current aviation collector generators features, reasons of anchor windings damages and their diagnosing methods is carried out. There were suggested the ways of reliability of a method of the pulse windings control of aviation direct current collector generators.